Emerging Technologies in Digital Museums: A Literature Review of Educational Application and Evaluation Methods - Yan, Lanye (Transactions on Social Science, Education and Humanities Research, 2024)
The rapid evolution of emerging technologies is fundamentally reshaping the educational landscape, with digital museums emerging as pivotal agents of educational innovation and progressively assuming vital roles in student learning. Through a systematic literature review, this study delves into the intricate relationship between new technologies and learning within digital museum contexts, along with the consequential impact of digital museums on student learning within the educational domain—an area of significant scholarly interest. The convergence of emerging technologies and the modernization of museum learning is increasingly ubiquitous, now integral to formal education. Initially, this paper scrutinizes the nexus between emerging technologies and the modernization of museum learning. Museums, revered as custodians of tradition and culture, are embracing digital media as conduits for transmitting cultural heritage and traditional knowledge to the younger generation. The application of emerging technologies heralds transformative possibilities for museum learning; for instance, Augmented Reality (AR) and Virtual Reality (VR) technologies afford students immersive experiences within historical settings or artifact displays, while big data analytics furnish museums with deeper insights into visitor behavior and enable personalized learning experiences. Furthermore, it expounds upon the tangible impacts of integrating digital museums with student learning activities. Technological innovations in digital museums not only enrich students’ learning encounters but also cultivate their autonomy and spirit of inquiry. Through digital exhibits and interactive learning engagements, students gain profound insights into subjects such as historical cultures and scientific phenomena, thereby amplifying their engagement and efficacy in learning. This paper endeavors to meticulously screen literature, unraveling the emerging technological applications in digital museums and their integration with student learning activities.